Polymerization of thiourea modified poly(acrylonitrile- Co-acrylic acid) for cationic dyes adsorption from single and binary solution - Adekanmi, Adeyi Abel (2019)
Synthetic organic dyes, especially cationic dyes are used extensively as colouring agents in many industries. The discharge of dye-bearing industrial effluents into hydrosphere, generate accumulation of unwanted colours in water, reducing photosynthesis of aqueous flora and causes biological attack towards aquatics. Besides, dye degradation products is also toxic, carcinogenic or mutagenic due to complex dye molecule structure. Hence, proper treatment of dye-containing industrial wastewater is a major environmental pollution issue for consideration. This study investigated the innovation of functional polymer-based adsorbent viz., thiourea modified poly(acrylonitrile-co-acrylic acid) that was used to sequestrate selected cationic dyes (malachite green (MG) and methylene blue (MB)) from model effluent by adsorption method. The poly(acrylonitrile-co-acrylic acid) copolymer was synthesized by redox polymerization of acrylonitrile (AN) and acrylic acid (AA) monomer, and further modified chemically with thiourea (TU) to produce TU modified poly(AN-co-AA) adsorbent. Then, single batch and fixed-bed adsorption experiments for each cationic dye, MG and MB were performed at varied operating conditions. Also, batch and packed-bed mode of adsorption for binary cationic dye solution onto TU modified poly(AN-co-AA) was studied. The adsorption process was found to be pH dependent and the initial dye concentration. The maximum single cationic dye uptake (%) for MG and MB were 92% and 96%, respectively at pH 9. The uptake of both MG and MB was an